2018
DOI: 10.1111/jfpe.12980
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extruder cooking conditions for the manufacture of fish feeds using response surface methodology

Abstract: A composite blend consisting of sunflower cake, maize germ, wheat bran, fresh water shrimps and cassava flour was extruded using a single-screw extruder to produce expanded fish feed pellets.The effects of temperature (80-120 C), die diameter (2-4 mm), and feed pre-conditioning time (50-150 s; steam 400 kPa) on properties of the pellets (expansion ratio, bulk density, floatability, durability, water absorption, water solubility, water stability, and in-vitro protein digestibility) were investigated using respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The Design-Expert 8.0.6 software (STAS-EASE Inc., Minneapolis, MN, USA) was employed for data analysis [19,20] . The lower and upper limits as well as coded levels of the above parameters (moisture content X 1 , preheating temperature X 2 and maximum compression force X 3 ) were selected as the independent variables and listed in Table 2.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The Design-Expert 8.0.6 software (STAS-EASE Inc., Minneapolis, MN, USA) was employed for data analysis [19,20] . The lower and upper limits as well as coded levels of the above parameters (moisture content X 1 , preheating temperature X 2 and maximum compression force X 3 ) were selected as the independent variables and listed in Table 2.…”
Section: Experimental Designmentioning
confidence: 99%
“…It has been found that when the moisture content is 10% w.b, the unit density decreased compared to pellets of other moisture content. The pelleting studies conducted by Guo et al [19] on four biomass grinds (barley, oat, canola and wheat straw) at different moisture contents of 9%, 12%, and 15% w.b. indicated that pellets made at 9% w.b.…”
Section: Unit Densitymentioning
confidence: 99%
“…It has been established that insect flour can replace fish meal in animal diets, corresponding to its amino acid profile. Insects are successfully included in the composition of food products for people, such as snacks [4,5,6]. Insects differ in their composition and structure from traditional types of feed and food raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…In another variant, they are used in the form of non-processed biomass. It should be noted that in the course of well-known studies of the extrusion of feeds containing grain and insect larvae, the latter were introduced into the feed in the form of fat-free and dehydrated protein-containing flour [4,5,6] or in the form of dehydrated and crushed mass [9]. Studies on the extrusion of larvae without their pretreatment or with minimal treatment (chitin isolation) have not been carried out before [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For qualitative grain extrusion it was necessary to moisten it that increased the cost of feed preparation [11]. The alternative method were to add other raw materials with high moisture content to grain and to extrude them jointly, which reduced the energy consumption of the process.…”
Section: Introductionmentioning
confidence: 99%